La expresión corporal y la motricidad gruesa en los niños del nivel inicial ii de la escuela de educación general básica “Santo Domingo de Cutuglagua” en el año lectivo 2022-2023 - Caiza Pilataxi, Mónica Patricia (2023)
The present investigation was carried out in the School of Basic General Education "Santo Domingo de Cutuglagua", located in the province of Pichincha, Mejía canton, Cutuglagua parish during the school year 2022-2023, having as study population the children of the Initial Level II , in which it was possible to observe and demonstrate the difficulty in corporal expression, therefore gross motor skills are affected, for this reason an alternative solution to the problem found in infants was proposed, this research was framed in the quantitative approach since that studies reality and allows quantifying the degree of development of body expression and gross motor skills, on the other hand the deductive method leads to an analysis of a whole until reaching the particular, in addition to the bibliographic method the relevant information is recorded from different sources, evidenced the progress of body expression and gross motor skills, on the other hand, techniques such as interviewing teachers and observation applied to infants, allowed to obtain positive results after their respective analysis and interpretation.